Observing lingering hyporheic storage using electrical resistivity: variations around stream restoration structures, Crabby Creek, PA. Issue 10 (18th April 2012) - Toran, Laura; Nyquist, Jonathan E.; Fang, Allison C.; Ryan, Robert J.; Rosenberry, Donald O.
Abstract Time‐lapse geophysical surveys can map lingering hyporheic storage by detecting changes in response to saline tracer. Tracer tests were conducted in Crabby Creek, an urban stream outside Philadelphia, to examine the influence of stream restoration structures and variable sediment thickness. We compared electrical resistivity surveys with extensive well sampling (57 wells) in two 13.5‐m‐long reaches, each with a step drop created by a J‐hook. The two step drops varied in tracer behaviour, based on both the well data and the geophysical data. The well data showed more variation in arrival time where the streambed sediment was thick and was more uniform where sediment was thin. The resistivity in the reach with thin sediment showed lingering tracer in the hyporheic zone both upstream and downstream from the J‐hook. In the second reach where the sediment was thicker, the lingering tracer in the hyporheic zone was more extensive downstream from the J‐hook. The contrasting results between the two reaches from both methods suggested that sediments influenced hyporheic exchange more than the step at this location. Resistivity inversion differed from well data in both reaches in that it showed evidence for tracer after well samples had returned to background, mapping lingering tracer either upstream or downstream of a step. We conclude that resistivity surveys may become an important tool for hyporheic zone characterization because they provide information on the extent of slow moving fluids in the hyporheic zone, which have the potential to enhance chemical reactions. Copyright © 2012 John Wiley & Sons, Ltd.